2020
DOI: 10.1111/jftr.12397
|View full text |Cite
|
Sign up to set email alerts
|

Multigenerational social support in the face of the COVID‐19 pandemic

Abstract: Research documents high levels of instrumental, financial, and expressive support exchanges within multigenerational families in the 21st century. The COVID‐19 pandemic poses unique challenges to support exchanges between the generations; however, the pandemic may provide opportunities for greater solidarity within families. In this review, we draw from theoretical perspectives that have been used to study family relationships to understand the implications of the pandemic for multigenerational families: the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 93 publications
4
57
0
3
Order By: Relevance
“…In line with our findings, a study conducted with older adults living in nursing homes identified several tensions experienced by participants' and resulting in a feeling of being "disconnected in a shrinking world" [35]. Next, our findings on relational ambivalence at an intergenerational level (the youth as both "friends" and "enemies" of the elderly) extends evidence from previous studies [36][37][38], and suggest that, compared to pre-pandemic conditions, a wider gap may emerge between young and old. This may have repercussions on exclusion and discrimination of older adults, and on intergenerational contrasts and tensions.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our findings, a study conducted with older adults living in nursing homes identified several tensions experienced by participants' and resulting in a feeling of being "disconnected in a shrinking world" [35]. Next, our findings on relational ambivalence at an intergenerational level (the youth as both "friends" and "enemies" of the elderly) extends evidence from previous studies [36][37][38], and suggest that, compared to pre-pandemic conditions, a wider gap may emerge between young and old. This may have repercussions on exclusion and discrimination of older adults, and on intergenerational contrasts and tensions.…”
Section: Discussionsupporting
confidence: 91%
“…Prior to the pandemic, studies demonstrated that the majority of older adults in Europe had at least weekly contact with their children living outside the parental home (Cooney & Dykstra 2013;Steinbach et al 2020), but because of the physical distancing measures that isolated older adults from their children, one could expect that the level of intergenerational interaction has generally decreased during the pandemic. However, this study also develops the alternative hypothesis that, rather than being a threat to parent-child ties, older adults had more frequent contact with their non-coresident children during the pandemic than before, fuelled by a shift towards more non-physical modes of communication (e.g., telephone and video calls, text messages, …) between generations (Arpino et al 2020a), intensified patterns of instrumental support requiring in-person contact (Gilligan et al 2020) and concerns over each other's health and wellbeing (Giovanis & Ozdamar 2020).…”
Section: Introductionmentioning
confidence: 64%
“…Physical distancing measures to curtail the spread of the virus may have weakened family relations, because they restricted older adults' opportunities to meet their non-coresident children in person. In addition, older adults might have been fearful of seeing their children, given their high risk profile (Settersten et al 2020) and adult children, in their turn, may also have preferred to minimize physical contact with their older parents to protect them from infection (Gilligan et al 2020). Also, mandated school and childcare closures meant that adult children experienced increased time demands at home (Del Boca et al 2020), potentially leaving less time to spend with their older parents.…”
Section: The Covid-19 Pandemic and Intergenerational Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…Intergenerational coresidence has been found to facilitate flows of support among family members during the current crisis in many other countries. In the United States, for example, the coresidence of young adults with their older parents increased as a result of the pandemic owing to the sharing of resources as a means of reducing expenditure ( Gilligan et al, 2020 ). In Spain, although no evidence of an increase in intergenerational coresidence has been found, probably because the arrangement is already relatively widespread, the willingness of older generations to provide financial and care assistance to younger generations did increase ( Ayuso et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%